Active Control of Vibration and Noise of Energy Equipment. Issue 2 (February 2020) - Li, Siting; Liu, Shuyong; Yang, Lihua
Abstract: Vibration and noise control is an important topic in the field of energy equipment research. The traditional passive control has better control effect in dealing with high frequency vibration noise, but it is not satisfactory in low frequency noise control. The active control solves this problem better. This article gives a reference for subsequent research in this field through a review method, which has certain reference value.